Quantifying the perceived safety of cyclists in Dublin - GHOSH, BIDISHA (My University, 2015)
In recent years, cycling has been recognised by policy makers and practitioners as a sustainable alternative to motorised travel. However, a lack of perceived safety associated with cycling may have inhibited its growth as a popular mode of transportation in urban environments. A questionnaire-based survey, conducted in Dublin city, found cyclists to perceive cycling in the city as less safe than driving. The survey responses were analysed in an ordered logistic regression framework to identify the determinants of their perceived safety in order to recommend possible policy interventions for improvement of these perceptions. A cyclist safety index is also proposed, which allows the perceptions of cyclists relative to driving to be quantified for consideration in transport network design and adaptation for cyclists.
PUBLISHED
Keywords: sustainability; health & safety; transport planning